Big bad wolf or man's best friend? Unmasking a false wolf aggression on humans. (September 2016) - Caniglia, R.; Galaverni, M.; Delogu, M.; Fabbri, E.; Musto, C.; Randi, E.
Abstract: The return of the wolf in its historical range is raising social conflicts with local communities for the perceived potential threat to people safety. In this study we applied molecular methods to solve an unusual case of wolf attack towards a man in the Northern Italian Apennines. We analysed seven biological samples, collected from the clothes of the injured man, using mtDNA sequences, the Amelogenin gene, 39 unlinked autosomal and four Y-linked microsatellites. Results indicated that the aggression was conducted by a male dog and not by a wolf nor a wolf x dog hybrid. Our findings were later confirmed by the victim, who confessed he had been attacked by the guard dog of a neighbour. The genetic profile of the owned dog perfectly matched with that identified from the samples previously collected. Our results prove once again that the wolf does not currently represent a risk for human safety in developed countries, whereas most animal aggressions are carried out by its domestic relative, the dog.